2010
DOI: 10.1080/10508422.2010.491743
|View full text |Cite
|
Sign up to set email alerts
|

“Doc, There's Something I Have To Tell You”: Patient Disclosure to Their Psychotherapist of Unprosecuted Murder and Other Violence

Abstract: The current investigation examines the incidence of clients telling their psychotherapists of committing violent crimes for which they have not been prosecuted. Thirteen percent of the psychologists surveyed indicated that on at least one occasion a client self-disclosed to them during a psychotherapy session that he/she had murdered someone, not including the killing of another person in the line of duty in the military or as a public peace officer. One third of the psychologists had clients self-disclose an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…What kind of strategies shall be taken for promoting the growth of visitors with different disclosure inclination? Confronted by the self-disclosure that may bring challenges, for instance, the disclosure of violent crimes (Walfish et al, 2010), these problems shall be further explored. In today's considerable development of psychological consulting, it is quite necessary for us to figure out the characteristics of seeking for help, so as to satisfy the practical demands.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…What kind of strategies shall be taken for promoting the growth of visitors with different disclosure inclination? Confronted by the self-disclosure that may bring challenges, for instance, the disclosure of violent crimes (Walfish et al, 2010), these problems shall be further explored. In today's considerable development of psychological consulting, it is quite necessary for us to figure out the characteristics of seeking for help, so as to satisfy the practical demands.…”
Section: Resultsmentioning
confidence: 99%
“…Scores are calculated according to the two dimensionalities "expected risk" and "expected effect" (four items), and the higher the score is, the higher the expectation will be. Some researchers also evaluate the self-disclosure of visitors by consulting the conditions of applying scales (Walfish, Barnett, Marlyere, & Zielke, 2010).…”
Section: Subjective Report Methodsmentioning
confidence: 99%
“…Equally, Pope and Tabachnick [38] implied fear of violence towards the client, the therapist or a third party was the most prevalent feeling in relation to reporting. Similarly, Walfish et al [30] described the fear of reporting unprosecuted criminal offences as very realistic. However, there are additional fears that are specific to nations in a transition from civil conflict to peace such as Northern Ireland, South Africa and Chile [21].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the United States of America, Pabian et al [24] found over seventy-six per cent of respondents were misinformed about their state laws, although respondents felt confident in the knowledge of their duty to warn obligations. Additionally, Walfish et al [30] found therapists in the US are generally aware of their duty to warn obligations when a third party is in danger, but are not clear on the issue of reporting past violence.…”
Section: Introductionmentioning
confidence: 99%